Gambaran Stress dan Strategi Coping pada Santri Tahfidz di Pondok Pesantren Al-Mahrusiyah Asrama al-‘Asyiqiyah - Uswatun Hasanah; Naeli Sa'adah (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2021)
In memorizing the Qur'an is not as easy as we imagine. Surely in the process there are many obstacles and obstacles, because the Al-Qur'an is kalamullah that not just anyone can memorize and practice it. The responsibility that is carried out by memorizing the Qur'an is also considered heavy because it will be attached to him until the end of his life. In addition, the activities of Islamic boarding schools such as formal schools, Madrasah Diniyah, Musyawaroh, Bahtsul, and others are things that hinder the memorization process. Because the activities in Islamic boarding schools are considered to be dense, the density of activities causes the body to become tired easily and can reduce adequate sleep time. And a lack of self-awareness that results in less conditioned muroja'ah. Starting from this busy life, a memorizer sometimes feels pressured by the demands and responsibilities he carries. Theoretically, this depressed state can be said as mild stress and in dealing with stress it can be called a coping strategy. The formulation of the problem in this study are: a) What are the stress conditions experienced by tahfidz students b) What are the causes of stress in tahfidz students c) How are coping strategies for tahfidz students. This research is a qualitative research. The discussion is theoretical and empirical, accompanied by an analysis that is in accordance with the conditions in the field. With a sample of 4 tahfidz students and the implementation of this research at the Al-Mahrusiyah Islamic Boarding School, Al-'Asyiqiyah Dormitory, Kediri Regency. Collecting data using observation, interviews, and documentation. While the data analysis technique uses data analysis techniques of data reduction, data presentation, and drawing conclusions. The results of the study, namely: each subject has almost the same stress symptoms but the stressors experienced are different and for each subject's coping, each subject is also almost the same but the behavior shown is different. In essence, the results of this study are that subjects I, II, and IV use the same type of coping, namely emotion focus coping and only one subject uses two types of coping, namely subject III. Subject III used emotion focus coping and also problem focus coping.